DYNAMICAL ANALYSIS OF SVEIR MODEL IN SPREAD OF THE MONKEYPOX DISEASE WITH TIME DELAY - Isnu Aji Saputro; Glagah Eskacakra Setyowisnu; Noor Sofiyati; Dian Puspita (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2025)
Monkeypox is an infectious disease whose spread is influenced by various epidemiological factors, one of which is the incubation period. This study developed a mathematical model of Monkeypox, SVEIR, by incorporating a time delay in the transition from an exposed individual to an infectious individual, representing the incubation period. Model analysis shows that the system has two equilibrium points: a disease-free state and an endemic state. Based on the simulation results, a threshold value (tau* ) is obtained, which plays a crucial role in disease control. If the incubation period is below the threshold ( tau<tau*), then R0>1 , and the disease will spread endemically. Conversely, if the incubation period exceeds the threshold (tau>tau* ), then R0<1 , and the disease will disappear from the population